2020
DOI: 10.1186/s12884-020-2779-4
|View full text |Cite
|
Sign up to set email alerts
|

Home-based telemonitoring versus hospital admission in high risk pregnancies: a qualitative study on women’s experiences

Abstract: Background: Hospital admission during pregnancy complications is considered to be an event of significant impact. Besides conventional in-clinic maternal and fetal monitoring, recent technologies enable home-based telemonitoring with self-measurements in high risk pregnancy. This study is part of a feasibility pilot to explore the usability and acceptability of telemonitoring and aims to gain insight in the experiences and preferences of high risk pregnant women concerning the novel strategy of telemonitoring,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 26 publications
1
47
0
1
Order By: Relevance
“…In 63% (12/19) of hospitals offering home-based monitoring, implementation of such monitoring was not preceded by a center-specific evaluation phase. However, home-based monitoring in these centers started mainly after the publication of the findings of 2 Dutch trials, which concluded positively about its patient safety and effects on satisfaction of care [7,8].…”
Section: Evaluation Of Usementioning
confidence: 99%
See 1 more Smart Citation
“…In 63% (12/19) of hospitals offering home-based monitoring, implementation of such monitoring was not preceded by a center-specific evaluation phase. However, home-based monitoring in these centers started mainly after the publication of the findings of 2 Dutch trials, which concluded positively about its patient safety and effects on satisfaction of care [7,8].…”
Section: Evaluation Of Usementioning
confidence: 99%
“…Ultimately, hospitalization is indicated in up to 11% of all pregnancies, usually extending to delivery and the postpartum period [5][6][7]. Antenatal admissions pose psychological stress to pregnant women because of separation from family and home, lack of activity, and feelings of uncertainty [8,9]. In addition, hospital admissions increase health care costs and workload, especially in high-income countries that are already experiencing difficulties as a result of professional staff shortage [10].…”
Section: Introductionmentioning
confidence: 99%
“…Given that pregnancy worries specific to the COVID-19 pandemic may play a role in satisfaction, providers may consider discussing with patients the extent to which a virtual prenatal care arrangement is a safe and alternative option for in-person visits, and how fetal monitoring will be maintained through in-person visits or remote monitoring equipment (blood pressure monitors, fetal heart monitoring, tape measures) should such monitoring take place virtually. Recent study findings suggest the accuracy, feasibility, and acceptability of home-based wireless fetal heart (FHR) monitoring systems among low and high-risk pregnant women (Heuvel et al, 2020 ; Porter et al, 2021 ), with evidence indicating home-based FHR readings to be equivalent to those obtained in the clinic setting (Porter et al, 2021 ). Moreover, there is data to suggest that most pregnant women are satisfied with home-based FHR monitoring (Heuvel et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent study findings suggest the accuracy, feasibility, and acceptability of home-based wireless fetal heart (FHR) monitoring systems among low and high-risk pregnant women (Heuvel et al, 2020 ; Porter et al, 2021 ), with evidence indicating home-based FHR readings to be equivalent to those obtained in the clinic setting (Porter et al, 2021 ). Moreover, there is data to suggest that most pregnant women are satisfied with home-based FHR monitoring (Heuvel et al, 2020 ). However, the consideration of such an arrangement should be fully discussed with the patient.…”
Section: Discussionmentioning
confidence: 99%
“…International guidelines including the European Society of Hypertension, American Heart Association, National Institute for Health and Care Excellence (NICE), and American Society of Hypertension guidelines, recommend self-monitoring for PE symptoms and recording of blood pressure for pregnant women at high risk for PE/E (HRPE/E) because of their potential benefits such as effective control of blood pressure, early risk identification, and treatment, and cost savings due to fewer hospital visits. [4][5][6] Self-monitoring also has a role in preventing conditions like white coat hypertension and masked hypertension in pregnant women at HRPE/E. WHO suggests home blood pressure monitoring for pregnant women at HRPE/E to detect changes in blood pressure between antenatal visits and to ensure care continuity.…”
Section: Open Accessmentioning
confidence: 99%